Pengaruh Rasio Keuangan dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015-2019 - Amilliatus Shobakhah; Aprilina Susandini (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to determine the effect of financial ratios in predicting profit growth in banking companies listed on the Indonesian stock exchange for the 2015-2019 period. The population of this study are banking companies listed on the Indonesian stock exchange for the 2015-2019. The sample of this study consisted of 40 companies with purposive sampling technique. The data used in this research is secondary data. Based on the r esults of this study indicate that the Curret Ratio has a positive and insignificant effect on Profit Growth, Total Assets Turn Over has a negative and significant effect on Profit Growth, Debt to Equity Ratio has a positive and insignificant effect on Profit Growth, Return On Assets has a positive and significant effect on Profit Growth. Simultaneously, this research has a joint effect on profit growth with a significant value of 0.000. The value of adjusted R Square is 34.2% while the remaining 65.8% is influenced by other variables not included in this study.